The Influence of Taboo Food Culture on Nutrition of Pregnant Women in the Konjo Community in Bulukumba District - As, Asrar (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Many cultures are believed to be irrational and hereditary to control themselves and their families to avoid danger. For this reason, abstinence, prohibition, or taboo is made which is nothing but a moral attitude to protect oneself from bad things that might happen. Objective: To determine the effect of taboo food culture on the nutritional status of pregnant women in the community in Bulukumba Regency. Methods: This study uses quantitative research, sampling techniques, and probability sampling techniques with a total sample of 60 respondents. Research results: Based on the results of the chi-square test, the p-value is 0.002 <0.005 that there is a relationship between taboo food culture and the nutritional status of pregnant women in accordance with the hypothesis, Ha can be accepted. Conclusion: Based on the results of research conducted in the Working Area of Puskesmas Batang, Kajang, Herlang Bulukumba Regency on 60 respondents it can be concluded that there is an influence of taboo food culture on the nutritional status of pregnant women in the Konjo community in Bulukumba Regency.